Cardiovascular and mortality risk in elderly Medicare beneficiaries treated with olmesartan versus other angiotensin receptor blockers. (26th November 2013) - Graham, David J.; Zhou, Esther H.; McKean, Stephen; Levenson, Mark; Calia, Katlyn; Gelperin, Kate; Ding, Xiao; MaCurdy, Thomas E.; Worrall, Chris; Kelman, Jeffrey A.
ABSTRACT Purpose In the randomized trial, Randomized Olmesartan and Diabetes Microalbuminuria Prevention, acute cardiovascular death was increased nearly fivefold in diabetic patients treated with high‐dose olmesartan, an angiotensin receptor blocker (ARB), compared with placebo. Methods Medicare beneficiaries were entered into new‐user cohorts of olmesartan or other ARBs and followed on therapy for occurrence of acute myocardial infarction, stroke, or death. Analyses focused on specific subgroups defined by diabetes status, ARB dose, and duration of therapy. Hazard ratios (HR) with 95% confidence intervals (CIs) were estimated using Cox proportional hazards regression, with other ARBs as reference. Results A total of 158 054 olmesartan and 724 673 other ARB users were followed for 54 285 and 260 390 person‐years, respectively, during which 9237 endpoint events occurred. Lower‐dose olmesartan was not associated with increased risk for any endpoint, regardless of duration of use. High‐dose olmesartan for 6 months or longer was associated with increased risk of death in patients with diabetes (HR 2.03, 95%CI 1.09–3.75, p = 0.02) and with reduced risk in nondiabetic patients (HR 0.46, 95%CI 0.24–0.86, p = 0.01). Some, but not all, sensitivity analyses suggested that selective prescribing of olmesartan to healthier patients (channeling bias) may have accounted for the reduced risk in nondiabetic patients. Conclusions High‐dose olmesartan was associated with an increased risk of death in diabetic patients treated for 6 months or longer and with a reduced risk of death in nondiabetic patients, when compared with use of other ARBs. This latter effect was probably because of selective prescribing of olmesartan to healthier patients, although effect modification cannot be excluded. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.